(untitled) (Psychology Travelogs, 2022)
The problem of bullying for today’s society (both in our country and in the world as a whole) is extremely widespread and relevant. In recent years, such a phenomenon as school bullying has gained special importance in educational practice, since the school does not remain aloof from the realities of life, and students follow models of interpersonal interaction that acquire a destructive character. This is caused, first of all, by the unstable situation in society: the crisis of the modern family, low social status, unemployment, the imposition of the ideology of consumption, society’s rejection of some moral values and the transition to new guidelines - all these are almost the most important contributing factors process of victimization of student youth. Modern schoolchildren can observe events in the country and, in a certain way, try on themselves models of behavior of adults to solve their problems and misunderstandings. More and more often it is becoming known about cases of aggressive and cruel relationships in school student groups, although for one reason or another they try to keep this problem quiet, not to publicize cases of bullying, it is not customary to discuss it. Under such conditions, the problem is not eliminated, but on the contrary, it acquires greater volumes of cruelty.